Preparation of ultrathin perovskite nanosheets by the exfoliation of H2CaTa2O7 for high-performance lead removal from water. Issue 114 (5th December 2016) - Wang, Yan; Ren, Yi; Luo, Jingjing; Hao, Qiaoyan; Li, Biao; Gao, Zhan; Hu, Yiwei; Lin, Dan; Tang, Kaibin
Abstract : Dimensionally tailored H2 CaTa2 O7 nanosheets show high adsorption efficiency for Pb(ii), as well as excellent regeneration properties. The large surface area and nonporous structure of the as-prepared nanosheets facilitate the uptake of Pb(ii). Abstract : Intercalation and delamination of two-dimensional solids are effective steps for exploiting their unique properties. Herein, the chemical exfoliation of the n -alcohol derivative of H2 CaTa2 O7 results in a colloidal suspension of monolayer nanosheets. Microscopic observation confirms the delamination of the parent perovskite. The thickness of the nanosheet obtained is 1.2 ± 0.1 nm. The dimensionally tailored H2 CaTa2 O7 nanosheets exhibit exceptional uptake of 300 mg g −1 Pb(ii ) ions at pH 5.0, and adsorption equilibrium is achieved in a short time span of 30 seconds. Experimental studies demonstrate that the treatment capacity for Pb(ii ) ions in simulated drinking water is 1.67 × 10 5 kg water per kg adsorbent. Desorption of Pb(ii ) ions is efficiently realized using 1 M HCl, which greatly reduces the cost associated with the regeneration. The large surface area of the ultrathin nanosheets and their nonporous structure facilitate the uptake of Pb(ii ) ions.